ACCELERATED CELL DEATH 6 Acts on Natural Leaf Senescence and Nitrogen Fluxes in Arabidopsis - Jasinski, Sophie; Fabrissin, Isabelle; Masson, Amandine; Marmagne, Anne; Lécureuil, Alain; Bill, Laurence; Chardon, Fabien (Frontiers in Plant Science, 2021)
As the last step of leaf development, senescence is a molecular process involving cell death mechanism. Leaf senescence is trigged by both internal age-dependent factors and environmental stresses. It must be tightly regulated for the plant to adopt a proper response to environmental variation and to allow the plant to recycle nutrients stored in senescing organs. However, little is known about factors that regulate both nutrients fluxes and plant senescence. Taking advantage of variation for natural leaf senescence between Arabidopsis thaliana accessions, Col-0 and Ct-1, we did a fine mapping of a QTL for leaf senescence and identified ACCELERATED CELL DEATH 6 (ACD6) as the causal gene. Using two near-isogeneic lines, differing solely around the ACD6 locus, we showed that ACD6 regulates rosette growth, leaf chlorophyll content as well as leaf nitrogen and carbon percentages. To unravel the role of ACD6 in N remobilization, the two isogenic lines and acd6 mutant were grown and labelled with 15N at the vegetative stage in order to determine 15N partitioning between plant organs at harvest. Results showed that N remobilization efficiency was significantly lower in all the genotypes with lower ACD6 activity irrespective of plant growth and productivity. Measurement of N uptake at vegetative and reproductive stages revealed that ACD6 did not modify N uptake efficiency but enhanced nitrogen translocation from root to silique. In this study, we have evidenced a new role of ACD6 in regulating both sequential and monocarpic senescences and disrupting the balance between N remobilization and N uptake that is required for a good seed filling.